The Success Rate and Complications of Central Venous Catheterization for General Surgery Patients in a Tertiary Hospital - Chanvitan, Supachai; Limsuwan, Nutchanon (The Thai Journal of Surgery, 2024)
Objective: Central venous catheterization (CVC) is one of the essential surgical procedures. It can lead to life-threatening complications. This prospective study aimed to evaluate the success rate and complications of central venous catheterization. Methods: This prospective observational cohort study collected data from patients undergoing central venous catheterization at the General Surgery Department, Rajavithi Hospital, from October 2020 to September 2022. Demographic information, the number of insertion attempts, operator details, success rates, the method used (ultrasound (US)-guided or anatomical landmark), and complications were recorded. Data analysis employed descriptive statistics, chi-square tests, student’s t-tests, and binary logistic regression. Result: 310 patients were enrolled. The overall success rate for central venous catheter (CVC) insertion was 95.2%. The US-guided method showed a significantly higher success rate compared to the anatomical landmark method (99.3% vs. 91.2%, P = 0.001), with 82.1% catheterized successfully on the first attempt using the US-guidance versus 50.9% with the landmark method (P < 0.001). The overall mechanical complication rate was 4.2%, including arterial puncture (1.6%), hematoma (0.3%), pneumothorax (0.3%), self-limiting arrhythmias (0.6%), and improper catheter placement (1.3%). The CRBSI rate was 7.7%, higher when occurring more than 15 days post-insertion (P < 0.001). Complication rates were significantly lower with the US-guided method compared to the landmark method (0.7% vs. 7.5%, P = 0.003). Procedures performed by 3rd to 4th-year residents also had lower complication rates compared to 1st to 2nd-year residents (0.3% vs. 3.9%, P = 0.023). Conclusion: The US-guided catheterization demonstrates a high success rate, fewer attempts, and reduced complication rates. Therefore, its regular use in catheterization procedures is strongly recommended.